Two classes of linear equations of discrete convolution type with harmonic singular operators. Issue 1 (2nd January 2016) - Li, Pingrun
Abstract : In this paper, we investigate two classes of linear equations of discrete convolution type with harmonic singular operator. Using the Laurent transform theory, we turn the above linear equations into Riemann boundary value problems. Then, the solutions of the equations are obtained in the class of Hölder continuous functions.